An Appraisal of Article 300 of the United Nations Convention on the Law of the Sea. (27th October 2022) - Kim, Hyun Jung; Norodom, Anne Thida
Abstract: The aim of this article is to clarify the meaning and scope of Article 300 (good faith and abuse of rights) of the United Nations Convention on the Law of the Sea (UNCLOS). Uncertainty about the meaning of Article 300 raises doubts about its raison d'être . It is insufficient to rely on the means of interpretation of treaties under Articles 31 and 32 of the Vienna Convention on the Law of Treaties and customary international law to understand Article 300 of UNCLOS. Therefore, this article analyzes relevant international cases brought before international courts and tribunals (ICTs) established under Part XV, Section 2 of UNCLOS to scrutinize the interpretation and application of Article 300. The first task of this article is to identify how ICTs have understood the structure of this provision and its character. After this general observation, this article answers the following questions: (1) Which state bears the burden of proof to invoke Article 300? (2) What conditions/steps fulfill Article 300's invocation? (3) In which circumstances do courts uphold or reject allegations that Article 300 has been breached? This article's findings allow for an appraisal of international judges' interpretations of the meaning and purpose of Article 300.